Semilinear elliptic equations having asymptotic limits at zero and infinity. (1999) - Perera, Kanishka; Schechter, Martin
Abstract : We obtain nontrivial solutions for semilinear elliptic boundary value problems having resonance both at zero and at infinity, when the nonlinear term has asymptotic limits.